Characterization of pulmonary rehabilitation programs in Canada in 2005 - Brooks, Dina (Pulsus Group Inc, 2007)
BACKGROUND: Pulmonary rehabilitation (PR) is recognized as the prevailing standard of care for patients with chronic respiratory conditions. National surveys of PR programs provide important information regarding the structure, content and organization of these programs. OBJECTIVE: To conduct a national survey to characterize adult PR across Canada, in terms of program distribution, utilization, content and outcome measures. METHODS: A cross-sectional descriptive study in which questionnaires were mailed to PR programs connected with hospitals or identified through the Canadian Lung Association was performed. RESULTS: Of the 98 PR programs identified, over 90% of patients in the programs had chronic obstructive pulmonary disease (COPD) and 57% of the programs were outpatient. Inpatient programs accounted for only 10% of the total. The main program components included supervised lower extremity strength (77%), cycle (72%) and treadmill (70%) training, education (75%) and breathing retraining (68%). Over 80% of patients completed their programs and 90% of patients were enrolled in a follow-up component. Physical therapists, dieticians, respiratory therapists and respirologists were the most commonly identified health care providers. The most commonly used outcome measures were the 6 min walk test and disease-specific quality of life questionnaires. CONCLUSION: There were similarities in program format, content, staffing, follow-up and funding among Canadian PR programs. The marked shortfall between the national PR capacity and the prevalence of COPD meant that only 1.2% of the COPD population had access to PR.